The selective influence of rhythmic cortical versus cerebellar transcranial stimulation on human physiological tremor. - Mehta, A; Brittain, J; Brown, P (2014)
The influence of central neuronal oscillators on human physiological tremor is controversial. To address this, transcranial alternating current stimulation (TACS) was delivered at peak tremor frequency to 12 healthy volunteers in a 2 × 2 crossover study. Two sites were stimulated [contralateral primary motor cortex (M1), vs ipsilateral cerebellum] while participants performed two types of tasks designed to probe the different manifestations of physiological tremor of the hand-kinetic and postural tremor. Tremor was measured by accelerometry. Cortical coherence with the accelerometry signal was also calculated in the absence of stimulation. The phase synchronization index, a measure of the phase entrainment of tremor, was calculated between stimulation and tremor waveforms. The amplitude modulation of tremor was similarly assessed. There was significant phase entrainment that was dependent both on tremor type and site of stimulation: M1 stimulation gave rise to phase entrainment of postural, but not kinetic, tremor, whereas cerebellar stimulation increased entrainment in both cases. There was no effect on tremor amplitude. Tremor accelerometry was shown to be coherent with the cortical EEG recorded during postural, but not kinetic, tremor. TACS modulates physiological tremor, and its effects are dependent both on tremor type and stimulation site. Accordingly, central oscillators play a significant role in two of the major manifestations of tremor in health.